1998
DOI: 10.1076/brhm.29.5.591.4823
|View full text |Cite
|
Sign up to set email alerts
|

Latitude and Social Habits as Determinants of the Distribution of Morning and Evening Types in Brazil

Abstract: Previous application of a Portuguese version of the Horne and Östberg (H&O) questionnaires in Brazil showed a displacement of the distribution of Morningness/Eveningness (M/E) types towards morningness, demanding a reclassification of the score's limits for each of the 5 possible M/E types. Among city, age and sex, city was the only factor determining significant group differences. In the present paper, the same version of the H&O's questionnaire was applied to a distinct population of 260 adults, balanced acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
11

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 11 publications
0
20
0
11
Order By: Relevance
“…The most widely used questionnaire is the Morningness-Eveningness Questionnaire (MEQ) of Horne and Östberg (10), although recently Roenneberg et al (11) have proposed a new one, the Munich Chronotype Questionnaire (MCTQ). The MEQ scores are likely to be biased by several factors, such as age, latitude and social habits (12,13). Moreover, several studies have also demonstrated that polymorphisms in clock genes might influence morningness-eveningness preference (14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…The most widely used questionnaire is the Morningness-Eveningness Questionnaire (MEQ) of Horne and Östberg (10), although recently Roenneberg et al (11) have proposed a new one, the Munich Chronotype Questionnaire (MCTQ). The MEQ scores are likely to be biased by several factors, such as age, latitude and social habits (12,13). Moreover, several studies have also demonstrated that polymorphisms in clock genes might influence morningness-eveningness preference (14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…The combination of genetic elements and sociodemographic, environmental and individual factors results in the preference for afternoon or morning social behaviors. 33 In this study, differences were identified in all shifts with respect to chronotype. However, in the sample analyzed, it was found that approximately 17% of night shift workers have morning characteristics and about 12% of workers who begin their activities at 7:30 am have afternoon characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Os cronotipos foram definidos por meio do questionário de matutinidade e vespertinidade de Horne e Ostberg 19 , traduzido para a população brasileira 3 . O questionário é composto por 19 questões de múltipla escolha que se referem a diferentes situações cotidianas em que os respondentes declaram sua preferência de horário na realização das atividades propostas.…”
Section: Participantes E Instrumentounclassified
“…Matutinos são aqueles que acordam cedo, espontaneamente, já aptos para desempenhar qualquer atividade, preferindo dormir mais cedo. Vespertinos preferem dormir tarde e acordar tarde 2,3 . Os ritmos endógenos dos matutinos estão em geral adiantados e os dos vespertinos atrasados em relação aos da população em geral.…”
Section: Introductionunclassified
See 1 more Smart Citation